PODE O JUDICIÁRIO AGIR CONCRETAMENTE ALÉM DOS LIMITES DE SUA COMPETÊNCIA - ATIVISMO JUDICIAL E JUDICIALISMO DA POLÍTICA - Aline Fonseca Franco; José de Oliveira Costa Filho (Universidade do Oeste Paulista, 2015)
The Social Democratic State and the program law inserted in the current Constitution caused an increase in demand to the judiciary, according the establishment of an awareness of rights. In this scenario, adding to the intense legislative activity, open to implement changes in the judiciary, verified by the change in the form of subsumption judge previously grounded in the fact the norm, adopting finalistic criteria hermeneutics, applying principles general rights. Thus, arise judicialization of law and judicial activism. The judiciary issued various decisions along these lines, which achieve effects on social and political issues. This position brings up discussions about the legitimacy of this action. This addresses the issue by bringing historical aspects and decisions presenting pro and con positions. It was concluded that there is no way to defend the total absence of activity of the judiciary, but unreasonable legal interference too, otherwise affront to republican principles.